Cancer in young people in the north of England, 1968-85: analysis by census wards. Issue 2 (April 1993) - Craft, A W; Parker, L; Openshaw, S; Charlton, M; Newell, J; Birch, J M; Blair, V
Abstract : OBJECTIVE–To determine whether the seeming excess of childhood leukaemia and lymphoma identified in Seascale, Cumbria, UK, remains unusual when put into a wider context. DESIGN–Analysis of cancer incidence by geographical area. SETTING–The north of England including the Northern and North Western Regional Health Authority regions and the Southport and South Sefton districts of the Mersey Regional Health Authority. SUBJECTS–Altogether 6686 cases of malignant disease in people under 25 years old. MEASUREMENTS AND MAIN RESULTS–Cases of cancer diagnosed before their 25th birthday between January 1968 and December 1985 identified from three regional cancer registries were allocated to a census ward on the basis of 'usual place of residence'. Population data were derived from the 1971 and 1981 censuses, and the cancer incidence was calculated for each ward. Of the 6686 cases, there were 1035 cases of acute lymphoblastic leukaemia and 361 of non-Hodgkins lymphoma. Wards were ranked by cancer incidence and Poisson probability, using different population bases. Seascale ward is the most highly ranked ward for acute lymphoblastic leukaemia for the time periods 1968-85 or 1968-76. It is not the most highly ranked for non-Hodgkins lymphoma. However, combining acute lymphoblastic leukaemia and non-Hodgkins lymphoma incidence gives an even more extreme position for Seascale. The most extreme Poisson probability for any of the analyses was that for brain tumours in the electoral ward of Ashton St Michael, Tameside (p = 0.000009). CONCLUSION–The incidence of acute lymphoblastic leukaemia and non-Hodgkins lymphoma in the Seascale ward remains high when put into a wider context. For other cancers there are wards with even more extreme Poisson probability values.